Examining the effects of the microglial PLCG2 P522R mutation by transplantation of human stem cell‐derived microglia in chimeric AD mice: Molecular and cell biology/stem cells, iPS cells. (7th December 2020) - Claes, Christel; Danhash, Emma; Hasselmann, Jonathan; Chadarevian, Jean Paul; Shabestari, Sepideh Kiani; Lim, Tau En; Tu, Christina; Silva, Jorge; Coburn, Morgan A.; Jairaman, Amit; Cahalan, Michael; Blurton‐Jones, Mathew; et al.
Abstract: Background: Genetic studies have uncovered several Alzheimer's Disease (AD) risk genes that are highly expressed in microglia, suggesting that immune dysregulation plays a critical role in the development and progression of AD. In line with this, a recently discovered polymorphism (P522R) in the microglia‐expressed gene Phospholipase C‐Gamma 2 (PLCG2) was shown to be protective for AD. Interestingly, PLCG2 codes for a protein that regulates the release of calcium from ER stores and is also a component of the downstream signaling pathway of TREM2, another microglial AD risk gene. This underscores the need to improve our understanding of microglial calcium signaling, the effects of AD risk genes on this pathway, and the impacts of PLCG2 and calcium signaling on human microglial function. Methods: CRISPR gene editing was used to produce isogenic iPSCs that express the AD protective mutation in PLCG2. Several in vitro assays were then performed to examine calcium signaling pathways and phagocytosis. PLCG2‐P522R and WT HPCs were also transplanted directly into xenotransplantation‐compatible mouse pups (MITRG‐5xfAD mice), where they readily differentiated into human microglia, exhibiting typical markers and morphology.. Xenotransplanted human microglia (x‐MG) were then examined by confocal microscopy and isolated from the brain for single‐cell RNA sequencing. Results: Thus far our in vitro studies suggest that the P522R coding mutation increases both basal cytosolic calcium concentrations and amyloid phagocytosis. Additional functional experiments are further examining the interactions between PLCG2 mutations and calcium signaling during the uptake of AD‐relevant substrates. In addition, single cell RNA sequencing studies of chimeric mice reveal that the P522R mutation leads to an increased percentage of human microglia that have adopted a disease‐associated microglial (DAM) phenotype in vivo . Conclusions: By combining iPSC‐microglia, CRISPR gene editing, and chimeric AD mice these studies have begun to uncover the impact of PLCG2 mutations on human microglial function and reveal that the protective P522R mutation increases Ab phagocytosis and promotes the adoption of a DAM‐like microglial response.